TINJAUAN PROSEDUR PENYELESAIAN KREDIT BERMASALAH PADA KREDIT PEMILIKAN RUMAH (KPR) DI BANK BTN KC TASIKMALAYA - Maharani Agustin; Annisa Desty Puspatriani (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2026)
Non-performing loans represent one of the risks faced by banks in their lending activities, particularly in housing loan (KPR) products. This study aims to analyze the procedures for resolving problematic housing loans and to identify the factors causing the decline in debtors’ repayment ability, as well as the obstacles encountered in the implementation of such procedures at PT Bank Tabungan Negara (Persero) Tbk, Tasikmalaya Branch Office. This research employs a qualitative method with a descriptive approach. Data were collected through direct observation and interviews with relevant parties within the bank. The results show that the procedures for resolving problematic loans are carried out through several stages, including submission of restructuring applications, document verification, analysis of the debtor’s repayment capacity, determination of restructuring schemes, approval, agreement signing, and post-restructuring monitoring. These procedures are supported by the application of the 3R concept, namely rescheduling, reconditioning, and restructuring, which are implemented flexibly according to the debtor’s condition. The findings also indicate that the decline in debtors’ repayment ability is mainly caused by decreased income, job loss, increased living expenses, and unstable economic conditions. In practice, several obstacles were identified, such as incomplete documentation, lack of debtor cooperation, and issues related to collateral ownership that has been transferred from the original debtor. Therefore, improved supervision, better communication, and stronger coordination between the bank and debtors are necessary to ensure the effectiveness of loan resolution procedures.